2022
DOI: 10.21203/rs.3.rs-1768951/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and safety of mucous fistula refeeding in preterm infants: An exploratory randomized controlled trial

Abstract: Background: This study aimed to evaluate whether mucous fistula refeeding (MFR) is safe and beneficial for the growth and intestinal adaptation of preterm infants with enterostomies.Methods: This exploratory randomized controlled trial enrolled infants born before 35 weeks’ gestation with enterostomy. If the stomal output was ≥ 40 mL/kg/day, infants were assigned to the high-output MFR group and received MFR. If the stoma output was < 40 mL/kg/day, infants were randomized to the normal-output MFR group or t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…These findings, as also discussed in the aforementioned reviews, could be explained by the physiological advantages of maintaining distal bowel function, which would promote peristalsis, cell hyperplasia and mucosal growth,31 facilitating feed tolerance and faster progression once feeds are restarted after reanastomosis. This is also supported by the preliminary findings of the study by Lee et al ,28 in which an increase in colonic diameter was described for the patients that received MFR compared with the control group. We also found lower rates of cholestasis, which could be explained by more physiological enterohepatic circulation and also as a secondary consequence of receiving less parenteral nutrition and tolerating feeds faster.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These findings, as also discussed in the aforementioned reviews, could be explained by the physiological advantages of maintaining distal bowel function, which would promote peristalsis, cell hyperplasia and mucosal growth,31 facilitating feed tolerance and faster progression once feeds are restarted after reanastomosis. This is also supported by the preliminary findings of the study by Lee et al ,28 in which an increase in colonic diameter was described for the patients that received MFR compared with the control group. We also found lower rates of cholestasis, which could be explained by more physiological enterohepatic circulation and also as a secondary consequence of receiving less parenteral nutrition and tolerating feeds faster.…”
Section: Discussionsupporting
confidence: 80%
“…The study by Haddock et al 27 reported three perforations, one of which led to the only death of a patient in the literature that can be attributed to the procedure. The preliminary findings of the trial by Lee et al 28 also reported one case of bowel perforation during manual reduction for stoma prolapse. These reports suggest providers to be extremely cautious with possible perforations during the manipulation of the catheters and requires further studies to be conducted prospectively to assess the safety profile of MFR.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Potential CRT-related complications and adverse events highlighted by the Bhat et al, 2020 systematic review were not seen in this study [11], with no device-related morbidity observed. A previous three-arm randomised controlled trial by Lee et al in 2023, investigating manual CRT on neonates with high output enterostomies, normal output enterostomies, and controls did have a similarly low number of events to this study, while highlighting the inefficiencies around previous CRT administration techniques [14]. These recent studies called attention to the robust weight gain and intestinal adaptation seen with neonates who are distally reinfused, in comparison to non-reinfused neonates, as seen dramatically again in our current data.…”
Section: Discussionsupporting
confidence: 50%
“…A further benefit of chyme reinfusion was advanced maturation of the distal (defunctioned) intestine, which enabled improve post-operative outcomes, including rapid return of bowel function (median 1 day) and no cases of ileus. Mismatch of an atrophied or growth-restricted defunctioned distal bowel segment presents a surgical challenge during restoration of continuity [8,14], and anecdotal feedback in this study provided positive indications that CRT can completely resolve this problem. This could be further assessed in future studies by including formal surgical feedback and comparisons of bowel morphology at the time of surgical restoration, and formally assessing surgical complication rates with and without CRT.…”
Section: Discussionmentioning
confidence: 72%